Customer Acceptance Toward The New Pertamina Self-Service System Using Technology Acceptance Model - Dean Al-ghazy, Rafi; Raafaldini Mirzanti, Isti (Journal of Business and Management, 2019)
Abstract. The present research is aimed at adapting the Technology Acceptance Model (TAM) to the use of Pertamina Self-Service in Bandung Area by examining the research and topics linked to this subject. In this study, the TAM model introduced by Davis in 1986. Thus this study sample consists of seven dimensions, which are the three following factors: quality (the quality of information and quality of service and the quality of the system), perceived ease of use the experience, the perceived usefulness, attitude toward use, behavioral intention to use and the actual system use. In light of this, the current study extended these necessary dimensions and factors in order to be expanded in line with the Self-Service business, especially in Pertamina’s Self-Service system in Bandung. The questionnaire used in this study was designed and developed based on an initial pretested survey distributed to a sample consisting of (352) customers that represent 3000 populations in a week. The data analysis gave the result that the acceptance of using Pertamina Self-Service is influenced by all the variable by (0.655) or equal to 65,5%. Besides the correlation between all variable among each other are between 0.344-0.714 which is have a strong correlation and related on the same direction. As for the variable, the strongest one is the Perceived Ease of Use which have (0.528) or equal to 52,8% value of contribution to influenced the Actual System Use. Keywords: TAM, Quality, SST, Actual Use, Ease